Teachers' Challenges and Strategies of Project-Based Learning Due to Limited Time for Mentoring Speaking Ability - Syahroni, Ali Imron (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2025)
The Project-Based Learning (PjBL) is a learning approach that focuses on students, where students are given more freedom in completing projects. However, the implementation of this method provides mixed perceptions among teachers. Some teachers face challenges in the form of limited assistance to students during the project completion process. In contrast, others perceive the method as supportive or challenging. This research explores teachers’ challenges with the Istiqlal English Course (IEC) in Probolinggo and the strategies used in implementing Project-Based Learning (PjBL), especially in teaching speaking skills. This research uses a qualitative approach with a case study design, involving two main instruments: observation and one-on-one interviews. Moreover, the results state four challenges: Vocabulary limitations, students’ time, motivation, difficulty in assessing individuals, and intensive monitoring. The strategies are: building student courage, observing participation, setting time limits, using a detailed plan, and combining PjBL and traditional methods. Based on these findings, it is recommended that teacher training programs include practical guidance on time management and student assessment within a Project-Based Learning (PjBL) framework to support more effective implementation in speaking instruction in English as a foreign language (EFL) classrooms.